Changes in volatiles of palm kernel oil before and after kernel roasting. (November 2016) - Zhang, Wencan; Wang, Rui; Yuan, Yonghong; Yang, Tiankui; Liu, Shaoquan
Abstract: Palm kernel oil (PKO) is obtained from the seeds of oil palm ( Elaeis guineensis Jackqu ). In this study, volatiles and aroma-active compounds of PKO were studied by head-space solid-phase microextraction/gas chromatography/mass spectrometry/flame ionisation detector (HS-SPME/GC/MS/FID) and solvent-assisted flavour evaporation -gas chromatography/olfactometry/mass spectrometry (SAFE-GC/O/MS), respectively. An optimised HS-SPME sampling method was obtained for extraction at 60 °C for 40 min. With this method, the volatiles of PKO from palm kernels subjected to different roasting times (up to 30 min) at 180 °C were analysed. Totally 73 volatiles were found, including 19 O-heterocyclic compounds (16 furans and 3 pyrans), 15 N-heterocyclic compounds (10 pyrazines and 5 others), 15 carbonyl compounds (5 aldehydes and 10 ketones), 11 acids, 4 alcohols, 3 esters, 3 sulphur and 3 volatile phenols. With the extension of roasting times, peak areas of O-heterocyclic compounds, N-heterocyclic compounds, aldehydes and cyclic ketones increased significantly whereas those of acids, alcohols and esters generally decreased. Results of GC/O/MS showed that 2-nonanone, octanoic acid and methyl octanoate were the most aroma-active compounds in unroasted PKO, while in roasted PKO, the most active volatiles were ethyl pyrazine, 2-nonanone, 2-hydroxy-3-methyl-2-cyclopenten-1-one, maltol, 2, 6-dimethylpyrazine, 2, 5-dimethylpyrazine, 2, 3-dimethylpyrazine, benzoic acid ethyl ester, octanoic acid, 5-methyl-2-furancarboxaldehyde and isomaltol. Highlights: Effect of roasting on volatiles of palm kernel oil (PKO) was studied. Volatiles changed dramatically in type and amount after roasting. Pyrazines, furans, pyrans and cyclic ketones were key volatiles in roasted PKO. Maillard and caramelisation reactions enhanced PKO aroma.